--And the clients went wild! : how savvy professionals win all the business they want - Kuzmeski, Maribeth (Wiley, 2010)
"While social media is doing much to change the marketing landscape, it doesn't mean you have to take an either/or approach between it and more traditional methods. ... And the Clients Went Wild! gives you the tools to take an eclectic approach and pick the best, most wildly successful marketing methods-traditional, online, or both-to win at a given marketing goal. And, whether by means of Facebook, Twitter, streaming video, or by old-fashioned word of mouth, public relations, or personal sales skill, the goal is to win, right? Don't throw out tried and true marketing techniques just for the sake of the new. Do what works! Perfect your marketing mix and win with ... And the Clients Went Wild!"--Resource description page